Batterer Intervention Programs in Spain: An Analysis of Their Effectiveness - Ferrer Pérez, Victòria A. (International journal of offender therapy and comparative criminology, 2018)
Intimate partner violence against women is a social and women’s health concern. Much effort has gone into providing services and support for victims of this violence. By contrast, intervention programs focusing on the batterers themselves have received far less attention. The purpose of this article is to provide a systematic review of the evidence regarding the effectiveness of batterer intervention programs (BIPs) implemented in Spain as provided by research published in peer-reviewed journals and scientific reports. The results obtained show that assessment focuses mainly on evaluating whether there is an improvement in the psychological variables of abusers. In cases where the rate of success or failure is analyzed, it is important to note the high drop-out rates observed, and the wide variability in success and improvement rates obtained. In summary, the results obtained in this revision allow to corroborate the assumption that associated with BIP is a lot of controversy, since its construction, its implementation, its assessment, and its effectiveness.